PEMANFAATAN CLOUD COMPUTING PADA APLIKASI NGEKOST BERBASIS ANDROID - Fathul Fata Deny Hp.; Hero Wintolo; Anggraini Kusumaningrum (Compiler, 2016)
Ngekost is an android-based boarding search application that utilizes the Internet as a medium of exchange data. The use of mobile android application as a tool to access something that is connected to the Internet to help users find a variety of information. Ngekost applications builtby using cloud computing as a technology that makes the Internet as a central storage server to manage data and information. One media system making cloud computing is to use a Virtual Private Server (VPS) as a virtual server. Applications Ngekost offers boarding house in the city of Yogyakarta, Malang, and Makassar with centralized image data on the storage servers each - each city boarding information and data stored on the database webserver. Services provided on the application can be accessed via the website owners to register them boarding, boarding entering data and images, while searches for boarding accessed via mobile android. The results of testing this application indicates that the application Ngekost by leveraging cloud computing can be usedas an information service for owners and seekers boarding based regional city o f Yogyakarta, Malang, and Makassar.